2023
DOI: 10.1108/lhs-08-2022-0089
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of primary health care leadership during the COVID-19 pandemic in Sweden: a qualitative study of managers’ experiences

Abstract: Purpose At the outbreak of the COVID-19 pandemic, health care was at the centre of the crisis. New demands made existing organizational practices and services obsolete. Primary health care had a great deal of responsibility for COVID-19-related care. The pandemic demanded effective leadership to manage the new difficulties. This paper aims to explore experiences and perceptions of managers in primary health care in relation to their efforts to manage the COVID-19 crisis in their everyday work. Design/methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Previous research on primary healthcare services during COVID-19 support several of the findings identified here. Similar challenges requiring leaders to adapt their ways of working such as insufficient contingency plans and infection control, lack of staffing, changing guidelines and routines and challenges related to information flow were found [17,31,[54][55][56]. Leader strategies to handle these challenges included reallocation of staff, providing support, provide training and distill and distribute information [16,31,55,57].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Previous research on primary healthcare services during COVID-19 support several of the findings identified here. Similar challenges requiring leaders to adapt their ways of working such as insufficient contingency plans and infection control, lack of staffing, changing guidelines and routines and challenges related to information flow were found [17,31,[54][55][56]. Leader strategies to handle these challenges included reallocation of staff, providing support, provide training and distill and distribute information [16,31,55,57].…”
Section: Discussionmentioning
confidence: 85%
“…Similar challenges requiring leaders to adapt their ways of working such as insufficient contingency plans and infection control, lack of staffing, changing guidelines and routines and challenges related to information flow were found [ 17 , 31 , 54 56 ]. Leader strategies to handle these challenges included reallocation of staff, providing support, provide training and distill and distribute information [ 16 , 31 , 55 , 57 ]. Some findings in this study, particularly related to the rural context, has not been found elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the current study, we emailed the participants (n=46) from the earlier studies, 7 9 all of whom had approved renewed contact after 2 years, asking them if they would like to participate again. Of the 46 original participants, 29 accepted ( table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The adaptations in PHC during the pandemic have been discussed regarding opinion-based lessons learnt 4 11 12 and in empirical studies based on data from frontline providers or managers in countries such as Brazil, 13 Benin, 14 UK 15 and Sweden. 7 9 Furthermore, multinational studies 16 17 have identified common challenges in PHC, such as managing information flows, and highlighted the differences in the approaches taken by PHC workers when dealing with patients with COVID-19 symptoms. However, the experiences of the pandemic among PHC providers and the impact on PHC operations in different countries may vary considerably depending on cultural and health system differences, emphasising the importance of national studies.…”
Section: Introductionmentioning
confidence: 99%